European developments in public sector human resource management - Hegewisch, A.; Larsen, Henrik Holt (Cranfield University, 1994)
This paper discusses national differences in HRM within the public sector in nine European countties. Drawing on data from the PW Cranfeld Survey of International Human Resource Management we examine the decentralisation of HR policy decisions and trends in the devolvement to line management of responsibility for human resource management. In particular we looked at trends in the compensation area, ie pay determination and merit/ performance related pay and its impact on performance appraisal.